A rare case of pituitary metastasis from hepatocellular carcinoma: case report and literature review - Cheng, Yuanchen; Feng, Ming (Frontiers in Oncology, 2023)
Presence of pituitary metastases (PMs) is a relatively rare clinical situation, especially when originating from hepatocellular carcinoma (HCC). A 73-year-old man presented with headaches, diplopia, and soon impaired vision, as well as gastrointestinal symptoms. Computed tomography (CT) and magnetic resonance imaging (MRI) of the brain revealed a space-occupying mass in the sellar region. The patient had a history of hepatocellular carcinoma and recent abdominal ultrasound and positron emission tomography (PET) indicated recurrence and metastases. Endoscopic transnasal transsphenoidal tumor excision was performed, and postoperative pathological report confirmed the diagnosis of HCC PM. In the literature review, 17 published cases of HCC PMs were summarized. Both the diagnosis and management of HCC PMs are difficult. Patients who had HCC-related history and new-onset headaches or diplopia should be inspected with a suspicion of metastatic lesions. Surgical intervention with transnasal endoscope is only recommended to ameliorate the symptoms and improve the life quality.